Limonium albuferae (Plumbaginaceae), a new polyploid species from the Eastern Iberian Peninsula - Ferrer-Gallego, Pedro Pablo; Roselló, Roberto; Rosato, Marcela; Rosselló, Josep Antoni; Laguna, Emilio (Phytotaxa, 2016)
A new species from Limonium (Plumbaginaceae), L. albuferae sp. nov., is described from the saline-sandy soils in the saltmarshes of the Eastern Iberian Peninsula (Devesa Albufera, Valencia province, Spain). The new species is triploid (2n = 26) and is closely related to the Western Mediterranean L. girardianum from which it morphologically differs by the major robustness, and overall dimensions of leaves, inflorescences, spikes and spikelets, and by the comparative smaller size of the outer and middle bracts.